2019
DOI: 10.1115/1.4043954
|View full text |Cite
|
Sign up to set email alerts
|

Rotor–Stator Interactions in a 2.5-Stage Axial Compressor—Part II: Impact of Aerodynamic Modeling on Forced Response

Abstract: The main objective of this study is the validation of numerical forced response predictions through experimental blade vibration measurements for higher order modes of a blade-integrated disk (blisk). To this end, a linearized and a nonlinear frequency domain CFD methods are used, as well as a tip timing measurement system. The focus is on the blade excitation by downstream vanes, in particular, because this study shows that the correct prediction of acoustic modes is of key importance in this case. The analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In addition to the primary excitations including the wakes from upstream stator rows and the potential fields from the downstream vanes, acoustic modes (also known as Tyler-Sofrin modes) generated by rotor-stator interactions occur at blade passing frequency and can contribute to rotor resonance. In a recent two-part study conducted by Terstegen et al [5] and Sanders et al [6], the existence of the acoustic Tyler-Sofrin modes was confirmed experimentally in a three-stage axial compressor, and the corresponding analysis demonstrated the importance of acoustic rotor-stator interactions for blade resonant response.…”
Section: Introductionmentioning
confidence: 86%
“…In addition to the primary excitations including the wakes from upstream stator rows and the potential fields from the downstream vanes, acoustic modes (also known as Tyler-Sofrin modes) generated by rotor-stator interactions occur at blade passing frequency and can contribute to rotor resonance. In a recent two-part study conducted by Terstegen et al [5] and Sanders et al [6], the existence of the acoustic Tyler-Sofrin modes was confirmed experimentally in a three-stage axial compressor, and the corresponding analysis demonstrated the importance of acoustic rotor-stator interactions for blade resonant response.…”
Section: Introductionmentioning
confidence: 86%
“…Many efforts have been made to accurately predict the blade response, including using a fluid-structure-coupled method [6][7][8], investigating the influence of the turbulence model [9], damping [6,7], boundary condition [8,9], and mesh densities [8,10], etc. These studies are helpful but mainly focus on the influence of numerical methods.…”
Section: Introductionmentioning
confidence: 99%
“…Schoenenborn [18] showed that the R1-S1-R2 interaction modes can lead to different blade excitations in the circumferential direction. Terstegen et al [9,19] investigated the effect of rotor-stator interactions on the rotor blade response of a 2.5-stage axial compressor. They performed detailed and comprehensive azimuthal mode analyses and stress predictions.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of heavy-duty gas turbines, the mass flow rate and single-stage load of compressors and the alternating aerodynamic force borne by blades continue to rise, resulting in increasingly prominent fluid-induced blade vibration [1]. The vibration problems faced by compressor blades mainly include the flutter and forced vibration caused by intake distortion [2,3], rotor-stator interference [4,5], stall and surge [6,7], and drop vortex [8,9]. The accidents caused by the forced vibration of gas turbines account for 25% of the total blade accidents, which cannot be ignored [10].…”
Section: Introductionmentioning
confidence: 99%